Radical Basque nationalism as a substitute religion - Tamayo Ayestarán, Alfredo (Razón y fe, 2018)
The effects and consequences of radical Basque nationalism experienced as a surrogate religion go beyond its religious significance. In addition to giving birth to new rituals and worldviews, their political heirs are reaching power quotas in which magnanimity is not part of this surrogate religion in practice.